Remodelling Business UMK “Bakso Sip”: Ten Types of Innovation - Hidhayah, Anysha Nur; Rahmi, Vembri Aulia; Kurniawan, Aries; Ismanto, Hadi (FKIP Universitas Lampung, 2023)
This research aims to find out how the implementation of